2022
DOI: 10.3389/fneur.2021.789589
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Lumbar Paraspinal Muscles in Young Adults With and Without Chronic Low Back Pain Based on Electrical Impedance Myography: A Cross-Sectional Study

Abstract: BackgroundLumbar paraspinal muscle (LPM) is important in spinal stabilization in patients with chronic low back pain (CLBP). However, the electrical properties of LPM in patients with CLBP remain unclear. Electrical impedance myography (EIM) is a novel and non-invasive technique that provides a simple quantitative evaluation of electrical properties of the LPM.PurposeThis study aimed to apply EIM to assess the electrical properties of the LPM between patients with CLBP and healthy control (HC).MethodsThirty pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…The skin over the lumbar region was prepped with an alcohol swab and left to dry to ensure optimal adherence of the single‐use, single‐tab electrodes. The electrode placement locations were uniform for all patients, following a previously described paraspinal electrode configuration, as shown in Figure 1 17 . Patients were instructed to remain still throughout the assessment and any direct contact with metal was avoided.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The skin over the lumbar region was prepped with an alcohol swab and left to dry to ensure optimal adherence of the single‐use, single‐tab electrodes. The electrode placement locations were uniform for all patients, following a previously described paraspinal electrode configuration, as shown in Figure 1 17 . Patients were instructed to remain still throughout the assessment and any direct contact with metal was avoided.…”
Section: Methodsmentioning
confidence: 99%
“…| 2073 placement locations were uniform for all patients, following a previously described paraspinal electrode configuration, as shown in Figure 1. 17 Patients were instructed to remain still throughout the assessment and any direct contact with metal was avoided. The assessment was performed three times consecutively on the both sides.…”
Section: Eim Measurement Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…The lumbar sEMG topographic map during these lumbar movements should be explored in the future. Thirdly, additional measurements of the low back muscles (e.g., muscle force, muscle thickness, muscle electrical impedance) should be explored in future studies [49][50][51], since there was no observed difference in muscle activation with and without a powered exoskeleton. Finally, the muscle fatigue state in this study is activated only in the holding task.…”
Section: E Limitationsmentioning
confidence: 99%